Upaya Pengurangan Produk Cacat Dengan Metode DMAIC Di PT.X - Nico Carol Harsoyo; Jani Raharjo (Jurnal Titra, 2019)
The DMAIC method is used to solve problems that exist in PT. X in terms of the quality of feed produced. The DMAIC method can identify the highest type of disability by using pareto charts, knowing the root of the problem using fishbone diagrams and knowing the solutions that can be implemented to minimize the occurrence of defective products using FMEA. The results of the study that the highest type of disability is abnormal texture consisting of streaks, high flour and pellet escapes. The root problem of the disability is the pelletizing process and the sieving process. The proposed improvement is to modify the engine and provide coaching to the operator to be more routine in maintaining cleanliness and checking the engine elements used for the production process.